The Judas Effect: Betrayal in Jean-Luc Godard’s Breathless - Vlad Dima (Studies in 20th & 21st Century Literature, 2016)
This article revisits the ending of Jean-Luc Godard’s Breathless (1960) in an attempt to untangle the complicated relationship between the two main characters, and to claim that they are characters that belong to no identifiable genre. Instead, they come to life as characters at the intersection point of existentialism, creationism, and two radically different genres, film noir and neorealism. In essence, they are characters without a genre, always out of place, and their existential drifting generates a Judas effect—a trope that establishes betrayal and sacrifice as necessary narrative tools and that suspends the classical (cinematic) Oedipal cycle.
Keywords: Betrayal; Godard; Cinema; Noir; Neorealism